2006
DOI: 10.1038/sj.bjp.0706902
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of glycogen synthase kinase‐3β attenuates the development of carrageenan‐induced lung injury in mice

Abstract: Background and purpose: Glycogen synthase kinase-3 (GSK-3) is a ubiquitous serine-threonine protein kinase that participates in a multitude of cellular processes and has recently been implicated in the pathophysiology of a number of diseases. The aim of this study was to investigate the effects of GSK-3b inhibition in a model of acute inflammation. Here, we have investigated the effects of TDZD-8, a potent and selective GSK-3b inhibitor, in a mouse model of carrageenan-induced pleurisy. Experimental approach: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
2
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 57 publications
4
46
2
3
Order By: Relevance
“…Recent studies have observed that the acute consumption of olive oil decreased the activation of NF-B system on mononuclear cells from healthy men (Perez-Martinez et al, 2007) and that 3,4-DHPEA-EA, trans-resveratrol, and hydroxytyrosol incubated with human umbilical vein endothelial cells inhibit LPS-triggered NF-B and AP-1 activation (Carluccio et al, 2003). Moreover, various experimental evidence have clearly suggested that NF-B plays a central role in the regulation of many genes responsible for the generation of mediators or proteins in acute lung inflammation associated with carrageenan administration (Cuzzocrea et al, 2006) such us TNF-, IL-1 , nitric oxide synthase inducible (iNOS) and COX-2. By inhibiting the activation of NF-B, the production of joint destructive inflammatory mediators may be reduced as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have observed that the acute consumption of olive oil decreased the activation of NF-B system on mononuclear cells from healthy men (Perez-Martinez et al, 2007) and that 3,4-DHPEA-EA, trans-resveratrol, and hydroxytyrosol incubated with human umbilical vein endothelial cells inhibit LPS-triggered NF-B and AP-1 activation (Carluccio et al, 2003). Moreover, various experimental evidence have clearly suggested that NF-B plays a central role in the regulation of many genes responsible for the generation of mediators or proteins in acute lung inflammation associated with carrageenan administration (Cuzzocrea et al, 2006) such us TNF-, IL-1 , nitric oxide synthase inducible (iNOS) and COX-2. By inhibiting the activation of NF-B, the production of joint destructive inflammatory mediators may be reduced as well.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of cytokines -Tumor Necrosis Factor-(TNF-) levels were evaluated in the plasma from CIA and sham mice as previously described (Cuzzocrea et al, 2006). The assay was carried out using a colorimetric commercial ELISA kit (Calbiochem-Novabiochem Co., Milan, Italy) with a lower detection limit of 10 pg/ml.…”
Section: Immunohistochemical Localization Of Nitrotyrosine Poly Adp mentioning
confidence: 99%
“…Recent evidence suggests that the activation of NF-KB may also be under the control of oxidant/antioxidant balance. Moreover, various experimental evidence has clearly suggested that NF-KB plays a central role in the regulation of many genes responsible for the generation of mediators or proteins in acute lung inflammation associated with carrageenan administration (23). NF-KB is normally sequestered in the cytoplasm, bound to regulatory protein IKBs.…”
Section: Discussionmentioning
confidence: 99%
“…GSK-3β is a serine/threonine protein kinase that participates in the regulation of cellular functions [26][27][28]. Upon external stimulation, GSK-3β is activation and phosphorylated, which may reduce enzyme activities and change the activity or function of its downstream components.…”
Section: Discussionmentioning
confidence: 99%